Effect of storage temperature and storage duration on biodiesel properties and characteristics - Zakaria, Hanis; Khalid, Amir; Sies, Mohamad Farid; Mustaffa, Norrizal; B., Manshoor (Trans Tech Publications, 2014)
Biodiesel based on vegetable oils offer the advantage being a sustainable and environmentally attractive alternative to conventional petroleum based fuel. Biodiesel is produced from any fat or oil such as soybean oil, through a refinery process called transesterification. The key issue in using vegetable oil-based fuels is oxidation stability, stoichiometric point, bio-fuel composition, antioxidants on the degradation and much oxygen with comparing to diesel gas oil. Biodiesel can be used as a pure fuel or blended with petroleum in any percentage but the standard storage and handling procedures used for biodiesel are the main issue due to the biodiesel fuel specifications. In the quest for fulfill the industry specifications standard; the fuel should be stored in a clean, dry and dark environment. In this research, three different storage temperature were study which are; low (0 – 5 °C), ambient, and high (40 – 50 °C). The key parameters that are required to store biodiesel are discussed, and the recent research advances are noted. Five types of biodiesel after storage all the samples for 2016 hours were tested plus with two product of combustion. Images analysis for combustion process was used to image appearances analysis. Under 2016 hours of storage duration, the effect of degradation was happen although the effect is not significance because the changes are still in acceptable ranges.